Ethnische Vielfalt und Arbeitsmarkterfolg - Ulf Rinne; Simone Schüller; Klaus F. Zimmermann (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– The economic potential of ethnic and cultural diversity is often underestimated. This paper summarizes a number of recent studies which show that 'soft' factors such as attitudes, perceptions and identities - and in particular ethnic identities - significantly affect economic outcomes. More specifically, the studies analyze the process of cultural integration over migrant generations as well as the process of job search and labor market reintegration of the unemployed. The economy can thus gain productivity and efficiency by recognizing and incorporating such multi-ethnic factors. Cultural assimilation that goes along with a loss of migrants' own cultural heritage does not appear to be the sole or dominant strategy of an economically successful integration. To tap the full potential of ethnic and cultural diversity, an increased cultural and ethnic open-mindedness of the native population is desirable.
Keywords: F22; J15; J61; 330; Einwanderer; multikulturelle Gesellschaft; ethnische Gruppe; Minderheiten; nationale Identität; Berufserfolg; Arbeitslose; berufliche Reintegration; interkulturelle Faktoren; kulturelle Faktoren; berufliche Integration; Inländer; interkulturelle Kompetenz; Schlüsselqualifikation; soziale Qualifikation; soziale Integration; kulturelle Identität; kulturelles Kapital; Assimilation; Segregation; Marginalität; ökonomische Faktoren